Konstruksi Politik Perempuan dalam Proses Pembentukan Pararem Desa Pakraman Megati Kelod (Jurnal Nawala Politika, 2022)
This study examines traditional Balinese women who cannot be separated from gender construction which politically positions them as a group that is always dominated by patriarchal structures. So this research was carried out to then see how the culture of placing them as patriarchal when indigenous women were given space in making decisions or policies at the customary level, especially in this case the pararem in Desa Pakraman Megati Kelod, Tabanan Regency, to get an actual picture of the political construction of indigenous women in the process of forming pararem policies within an institutional structure. This study uses a type of qualitative method with the approach taken in this study, namely case study research. The findings show that the role of women in the Pakraman Megati Kelod Village in the process of forming perarem is still very suboptimal. Several factors hindered the role of women in the pararem formation process, such as unsupportive social conditions, lack of courage in expressing their voices in forums and the extent to which their capacities were controlled. These factors then prevent women from contributing further in the public sphere such as Paruman.